Pendampingan Guru SMKN 1 Tukak Sadai dalam Penggunaan Platform Digital untuk Pembelajaran Berbasis Project - Dzalfa Tsalsabila Rhamadiyanti; Aditya Ahmad Fauzi; Fithriawan Nugroho; Fitriyanti Fitriyanti (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aimed to strengthen teachers’ competencies in utilizing digital platforms to support project-based learning at a vocational high school. The background of this activity was the limited ability of teachers to manage project-based learning in a structured and systematic manner using digital platforms. The method employed was participatory mentoring, involving needs analysis, activity planning, implementation of digital platform mentoring, monitoring and evaluation, and reflection with follow-up actions. The participants were teachers of SMK Negeri 1 Tukak Sadai, Bangka Barat. The results indicated an improvement in teachers’ understanding and skills in designing, managing, and evaluating project-based learning using digital platforms. Teachers became more confident in integrating technology into learning processes and demonstrated better organization of project activities. This activity contributed to enhancing teachers’ digital competencies and improving the quality of project-based learning practices in vocational education. The findings suggest that participatory mentoring is an effective approach to supporting sustainable digital learning innovation in vocational schools.